DESIGN OF ROLLER MECHANISMS FOR ORIENTATION OF FLAT FOOTWEAR PARTS DURING THE PROCESSING PROCESS - KARMALITA, ANATOLII; DZIAVORUK, OLEKSANDR; PUNDYK, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
For analytical and experimental study of the process of controlling the position and orientation of flat parts with different frictional properties of surfaces using two rolls, it is necessary, first of all, to build a physical and mathematical model of the interaction of rolls with the surfaces of these parts. The article is devoted to the basics of building such models, taking into account all the factors on which this process depends. Quite a lot of work has been devoted to the study of the frictional properties of materials used for shoe parts. Analyzing them, we can conclude that most shoe materials have different frictional properties of the front and back surfaces. The design of roll mechanisms is considered on the example of designing the mechanism of transporting rolls of machines for splitting and leveling the thickness of the bottom and top parts of shoes, machines for grinding bottom parts and other pass-through machines. In the process of designing roll mechanisms, it is necessary to know the forces that arise during transportation and processing of products. From the physical model of the process, it was found that the transportation conditions depend on the design features of the roller mechanisms and the physical and mechanical properties of the material from which the flat parts are made. As a result of the analytical studies presented in the article, formulas were obtained that relate the forces that expand the rollers and can be created by springs, and the radii of the rollers; the geometric parameters of the part being transported, and the physical and mechanical properties of the materials from which the parts are made. If rollers are used to control the position and orientation of flat parts by the frictional properties of the surfaces, then these formulas can also be used, but it should be taken into account that the rollers will rotate in opposite directions.